Occupational Stress, Burnout, and Depression in Women in Healthcare During COVID-19 Pandemic: Rapid Scoping Review - Sriharan, Abi; Ratnapalan, Savithiri; Tricco, Andrea C.; Lupea, Doina; Ayala, Ana Patricia; Pang, Hilary; Lee, Dongjoo Daniel (Frontiers in Global Women's Health, 2020)
The overall objectives of this rapid scoping review are to (a) identify the common triggers of stress, burnout, and depression faced by women in health care during the COVID-19 pandemic, and (b) explore individual-, organizational-, and systems-level interventions that can support the well-being of women HCWs during a pandemic. This review was guided by the JBI guide to scoping reviews. A systematic search of literature databases was conducted until June 12, 2020. Two reviewers independently assessed full-text articles according to predefined criteria. We included review articles and primary studies that reported on stress, burnout, and depression in HCWs; that primarily focused on women; and that included the percentage or number of women included. All English language studies from any geographical setting where COVID-19 has affected the population were reviewed. Studies reporting on mental health outcomes, interventions to support mental health well-being were included. Results of the 2,803 papers found, 28 were included. The triggers of stress, burnout and depression are grouped under individual-, organizational-, and systems-level factors. There is a limited amount of evidence on effective interventions that prevents anxiety, stress, burnout and depression during a pandemic. Our preliminary findings show that women HCWs are at increased risk for stress, burnout, and depression during the COVID-19 pandemic. These negative outcomes are triggered by factors such as lack of social support; family status; access to personal protective equipment or high workload rapidly changing public health guidelines, and a lack of recognition at work.